Evaluating the impact of gamification on user engagement in B2B SaaS onboarding - Nevalainen, Viivi (My University, 2025)
As the Software as a Service (SaaS) market becomes increasingly saturated, effective onboarding has emerged as a critical factor for enhancing user engagement and reducing customer churn. This is particularly important in the complex, multi stakeholder environments of B2B products, where first impressions are vital and switching between providers is easy. Given that the SaaS and gaming industries share challenges such as discoverability issues, early user retention and intuitive design, this thesis investigates the impact of gamification on user engagement during the onboarding phase of B2B SaaS products. Thesis follows the definition of gamification as the use of game design elements in non-game contexts. The research is grounded in a theoretical framework that defines SaaS onboarding through four core elements: statement of purpose, user identification, informational support, and conversion event. The study combines a literature review on SaaS and game design with a multiple case analysis of three B2B SaaS products (Cuckoo, ProdPad, and Todoist). Additionally, semi-structured user interviews with seven B2B participants exploring Todoist are conducted. The interviews are analyzed thematically using the onboarding element framework to gather user-centered insights on the role of gamification in SaaS onboarding. Findings show that forward gamification elements, such as visual progress indicators and contextual guidance, enhance clarity and user motivation during onboarding. In contrast, reward-based elements, such as points or levels, receive mixed responses depending on user autonomy and their relevance to work-related goals. The study underscores the importance of layering gamified features on top of a strong UX foundation and offers practical implications for SaaS providers aiming to differentiate their onboarding experiences from competitiors and foster long-term user engagement in B2B contexts.
Keywords: SaaS, B2B, gamification, onboarding, user engagement